Invasive Plant Ecology and Management Linking Processes to Practice CABI Invasives Series, Volume 2 - Monaco, Thomas A.; Sheley, Roger L.; Ebooks Corporation (Wallingford : CABI, 2012)
Bringing together ecology and management of invasive plants within natural and agricultural ecosystems, this book bridges the knowledge gap between the processes operating within ecosystems and the practices used to prevent, contain, control and eradicate invasive plant species. The book targets key processes that can be managed, the impact of invasive plants on these ecosystem processes and illustrates how adopting ecologically based principles can influence the ecosystem and lead to effective land management. It is suitable for researchers, practitioners and students of ecology, invasive species management and weed science.
Contenido: PART II: PRINCIPLES AND PRACTICES TO INFLUENCE ECOSYSTEM CHANGE6 Weather Variability, Ecological Processes, and Optimization of Soil Micro-environment for Rangeland Restoration; 7 The Effects of Plant-Soil Feedbacks on Invasive Plants: Mechanisms and Potential Management Options; 8 Species Performance: the Relationship Between Nutrient Availability, Life History Traits, and Stress; 9 Reducing
Libro electronico adquirido a perpetuidad con la editorial CABI
Keywords: PLANTAS INVASORAS -- CONTROL; PLANTAS INVASORAS -- ECOLOGIA